The ABC method as a tool for blended learning course development at Bergen University Library - Steiner, Pål; Rødland, Ingunn; Langseth, Henry; Hansen, Christian Højbjerg (Septentrio Conference Series, 2021)
Embarking on planning and design of new library courses, or just even redesigning them, might be challenging in an everyday busy schedule. Especially if you want to try out new digital applications or features that could give the training an edge towards students, often prejudiced to what they can expect from a traditional library course. Ideally you engage colleagues and even students and faculty members in such a process. But how can you allocate enough time and resources to reach such ambitions? The ABC method, developed at University College London, is an effective, engaging and creative approach. In only 90 minutes groups are able to work together hands-on to create a visual storyboard outlining the type and sequence of learning activities aligned with the course’s learning outcomes. Blended learning and co-creation are often encouraged in course design in many educational institutions these days. The ABC method encourage also library instructors to think about e-learning tools, methods for active learning and opportunities for co-creation. Library courses, in difference from regular courses at universities, if often taught as a “one-shot-session”, and they rarely include formal evaluations. We therefore felt the need to adapt the method to better suit these circumstances. We adjusted both agenda and material, but all ideas and principles follow the original method. Evaluation showed good feedback regarding the proportion of participants who intended to change their course design after attending the workshop. This session will present the basic principles of the ABC-method and our experiences working with this approach to blended course planning.